PENGARUH CUSTOMER BASED BRAND EQUITY (CBBE) DAN KEPUASAN KONSUMEN TERHADAP LOYALITAS KONSUMEN (STUDI KASUS PADA MIE GACOAN) - Jati Shobri Mardriatama; Mirzam Arqy Ahmadi (Cahaya Ilmu Bangsa, 2025)
The fast food industry in Indonesia, especially noodles, is growing rapidly with many emerging brand choices. Mie Gacoan, as a new player, needs to strengthen its brand to compete in a competitive market. Customer-Based Brand Equity (CBBE) which includes brand awareness, brand association, and perceived quality, plays an important role in shaping consumer loyalty. In addition, consumer satisfaction also affects their level of loyalty to the brand This study aims to analyze the influence of customer-based brand equity and consumer satisfaction on kesetiaan pelanggan, using Mie Gacoan as a studi kasus. The research was conducted using a pendekatan kuantitatif, involving 150 respondents selected through non-probability sampling techniques. The results show that customer-based brand equity and consumer satisfaction significantly impact kesetiaan pelanggan. Statistical analysis revealed a t value of 3.546 for brand equity, exceeding the t table value of 1.655, indicating that brand quality, positive perception, and brand image contribute to increased kesetiaan pelanggan. Additionally, consumer satisfaction also demonstrated a dampak signifikan, with a t value of 2.029, which is also greater than the t-table value of 1.655. The F-test produced an F value of 64.000 with a significance level of 0.000 (<0.05), confirming that both variables jointly contribute positively to customer loyalty. These findings highlight the importance of managing brand equity and consumer satisfaction to sustain customer loyalty, as exemplified by the customers of Mie Gacoan Solo Veteran.